1999
DOI: 10.1161/01.cir.99.16.2085
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Impact of Preconditioning During PTCA on Creatine Kinase Release

Abstract: A standardized protocol to elicit preconditioning during PTCA results in a significant reduction in the rate of CK elevation in a high-risk population. These observations support the clinical relevance of ischemic preconditioning in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 39 publications
0
35
1
1
Order By: Relevance
“…3,13,22,23) Appropriate balloon ischemia has been shown to suppress lactate production during coronary angioplasty in patients with stable angina pectoris 3) and creatine kinase elevation after coronary angioplasty in patients with unstable ischemic syndromes. 22) Yasuda, et al 13) reported that pre-administration of nicorandil suppresses lactate production during angioplasty, suggesting that pharmacological preconditioning is induced by nicorandil. Jenkins, et al 23) reported that short periods of ischemia at the beginning of the revascularization operation reduce TnT release in patients undergoing coronary artery bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3,13,22,23) Appropriate balloon ischemia has been shown to suppress lactate production during coronary angioplasty in patients with stable angina pectoris 3) and creatine kinase elevation after coronary angioplasty in patients with unstable ischemic syndromes. 22) Yasuda, et al 13) reported that pre-administration of nicorandil suppresses lactate production during angioplasty, suggesting that pharmacological preconditioning is induced by nicorandil. Jenkins, et al 23) reported that short periods of ischemia at the beginning of the revascularization operation reduce TnT release in patients undergoing coronary artery bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Less pain was the reported clinical end point. 41,42 There were then several smaller proof-of-concept studies on ischemic preconditioning in patients undergoing surgical revascularization by CABG or valve surgery.…”
Section: Ischemic Preconditioningmentioning
confidence: 99%
“…It is known that exercise can mimic the protective effect of IP (9,12,21,51). Evidence for preconditioning in humans derives also from in vitro studies (42) and observations made during coronary angioplasty and cardiac surgery (12,21,51).…”
Section: Physiological Significance Of the Findings In Cardioprotectionmentioning
confidence: 99%
“…Evidence for preconditioning in humans derives also from in vitro studies (42) and observations made during coronary angioplasty and cardiac surgery (12,21,51). Also, the warm-up phenomenon (i.e., enhanced resistance to further ischemia in patients suffering from angina a few minutes after a previous effort) has been attributed to a preconditioning-like effect (9,46).…”
Section: Physiological Significance Of the Findings In Cardioprotectionmentioning
confidence: 99%